Cerebral Amyloid Deposition is Associated with Gait Parameters in the Mayo Clinic Study of Aging - Wennberg, Alexandra M. V. (J Am Geriatr Soc, 2016)
BACKGROUND/OBJECTIVES: To determine the cross-sectional association between cerebral amyloid-beta (Aβ) deposition and gait. DESIGN: Cross-sectional. SETTING: Population-based cohort study in Olmsted County, MN. PARTICIPANTS: Cognitively normal individuals (n=611), aged 50-69 years, enrolled in the Mayo Clinic Study of Aging with concurrent PiB-PET imaging and gait assessment. Participants with a history of stroke, alcoholism, Parkinson’s disease, subdural hematoma, traumatic brain injury, or normal pressure hydrocephalus were excluded. MEASUREMENTS: PiB-PET SUVR was measured in prefrontal, orbitofrontal, parietal, temporal, anterior cingulate, posterior cingulate, and motor-specific regions of interest (ROIs). Gait parameters (speed, cadence, stride length, double support time, and intra-individual stance time variability) were measured using GAITRite® instrumentation. Linear regression models were adjusted for age, sex, body mass index, education, APOE ε4 allele, Charlson comorbidity index, and depression. In secondary analyses, we additionally adjusted for neurodegeneration (hippocampal volume, FDG PET SUVR, and cortical thickness) in AD-associated regions. RESULTS: In fully adjusted models including neuroimaging measures of neurodegeneration, higher PiB-PET SUVR across all ROIs was associated with slower gait speed (P < .05 except for the parietal ROI), lower cadence and longer double support time (P ≤ .05 except for the motor ROI), and greater stance time variability (P < .05). In sex-stratified analyses, the association between higher PiB-PET SUVR across all ROIs and measures of gait was only present among women. CONCLUSION: PiB-PET SUVR across ROIs, independent of general measures of AD-associated neurodegeneration, is associated with poorer performance on multiple gait parameters among cognitively normal women, aged 50-69 years. Longitudinal studies are needed to determine whether Aβ predicts gait decline in both women and men.